1999
DOI: 10.1097/00005721-199907000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Living With Postpartum Depression: The Father's Experience

Abstract: Health care professionals need to design interventions that are more supportive of men, for men also suffer when their spouses experience PPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
66
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 5 publications
10
66
0
8
Order By: Relevance
“…Postpartum depressive disorder rates in Turkey are similar to other countries' data and varies between 14% -36% (6,21,28,29). Prevelance of postpartum depression is reported to be between 13%-34.7% (5,10,13,(30)(31)(32)(33).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Postpartum depressive disorder rates in Turkey are similar to other countries' data and varies between 14% -36% (6,21,28,29). Prevelance of postpartum depression is reported to be between 13%-34.7% (5,10,13,(30)(31)(32)(33).…”
Section: Discussionsupporting
confidence: 72%
“…Maternal depression has a negative impact on the quality of the mother-infant relationship, cognitive and emotional development of child and their relationship with family (12,20,21). Children of depressed mothers are under increased risk for a variety of psychiatric problems, behavioral disturbances and social and achievement problems (22).…”
mentioning
confidence: 99%
“…For instance, fathers have reported that their partner's postnatal depression had created a tense and hostile family environment, with unequal divisions of labour, wherein their contribution was unappreciated (e.g. Meighan, Davis, Thomas, & Droppleman, 1999;Webster, 2002) and their child care criticised or undermined (Morgan, Matthey, Barnett, & Richardson, 1997). Furthermore, Meighan et al (1999) found that men fathering in this context perceived their own lives as unpredictable and out of control, with irreparable damage to the partner relationship and a desire to avoid having more children in such a fragile context.…”
Section: Introductionmentioning
confidence: 99%
“…A convivência diária com uma mulher deprimida pode desencadear no homem o aparecimento de doenças do foro psiquiátrico, como perturbações da ansiedade, episódios de depressão generalizada ou ainda o desenvolvimento de humor depressivo (Meighan, Davis, Thomas & Droppelman, 1999). Quer o envolvimento excessivo, com o filho recém-nascido, que reduz substancialmente o tempo que dedica ao companheiro (Barnes, 2006), quer a hipercrítica constante da mãe relativa à falta de envolvimento paterno, fazem com que o pai se sinta excluído e abandonado, favorecendo o aparecimento de sintomatologia depressiva.…”
Section: El Comportamento Parental De Compañeros De Mujeres Con Depreunclassified
“…Quer o envolvimento excessivo, com o filho recém-nascido, que reduz substancialmente o tempo que dedica ao companheiro (Barnes, 2006), quer a hipercrítica constante da mãe relativa à falta de envolvimento paterno, fazem com que o pai se sinta excluído e abandonado, favorecendo o aparecimento de sintomatologia depressiva. Apesar dos homens serem menos propensos a desenvolver depressão pós-parto, ela também pode manifestar-se em figuras masculinas, apresentando sintomas físicos e psicológicos idênticos aos maternos (Bielawska-Batorowicz & Kossakowska-Petrycka 2006; Meighan, Davis, Thomas & Droppelman, 1999;Zelkowitz & Milet, 2001).…”
Section: El Comportamento Parental De Compañeros De Mujeres Con Depreunclassified